2023
DOI: 10.1021/acs.analchem.3c01356
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Isotopic Composition of Aqueous Mercury in a Paddy Ecosystem Using Diffusive Gradients in Thin Films

Hongqian Yin,
Heng Yao,
Wei Yuan
et al.

Abstract: Measuring the isotopic composition of Hg in natural waters is challenging due to the ultratrace level of aqueous Hg (ng L–1). At least 5 ng of Hg mass is required for Hg isotopic analysis. Given the low Hg concentration in natural waters, a large volume of water (>10 L) is typically needed. The conventional grab sampling method is time-consuming, laborious, and prone to contamination during transportation and preconcentration steps. In this study, a DGT (diffusive gradients in thin films) method based on amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…The results showed that the Hg concentration in the overlying water before sampling in batches 2–8 was 6.3 ± 0.4 ng L –1 (1SD, n = 7), which was comparable ( p > 0.05) to the Hg concentration in the initial overlying water (6.9 ± 1.6 ng L –1 ). Similarly, the Hg isotopic composition (δ 202 Hg = −0.71 ± 0.14‰, Δ 199 Hg = 0.33 ± 0.03‰, 2SD, n = 7) of the overlying water before sampling in batches 2–8 was also not significantly ( p > 0.05) different from the Hg isotopic composition (δ 202 Hg = −0.67 ± 0.21‰, Δ 199 Hg = 0.29 ± 0.38‰) at the beginning. The isotopic signatures of the product Hg(0) during the in situ Hg(II) photoreduction and abiotic dark reduction processes are shown in Table S2.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The results showed that the Hg concentration in the overlying water before sampling in batches 2–8 was 6.3 ± 0.4 ng L –1 (1SD, n = 7), which was comparable ( p > 0.05) to the Hg concentration in the initial overlying water (6.9 ± 1.6 ng L –1 ). Similarly, the Hg isotopic composition (δ 202 Hg = −0.71 ± 0.14‰, Δ 199 Hg = 0.33 ± 0.03‰, 2SD, n = 7) of the overlying water before sampling in batches 2–8 was also not significantly ( p > 0.05) different from the Hg isotopic composition (δ 202 Hg = −0.67 ± 0.21‰, Δ 199 Hg = 0.29 ± 0.38‰) at the beginning. The isotopic signatures of the product Hg(0) during the in situ Hg(II) photoreduction and abiotic dark reduction processes are shown in Table S2.…”
Section: Resultsmentioning
confidence: 88%
“…The average Hg isotopic compositions of the overlying water (δ 202 Hg = −0.67 ± 0.21‰, Δ 199 Hg = 0.29 ± 0.38‰) in the investigated rice paddy during the same sampling periods were reported by Yin et al . The enrichment factor for microbial reduction (ε 202 Hg = −1.51 ± 0.24‰, E 199 Hg = 0) was determined in Section .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation